2020
DOI: 10.21276/apjhs.2020.7.2.5
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Immunization Coverage in Children in Urban Slums of Western Maharashtra

Abstract: Background: Children in urban slums suffer accentuated vulnerability to illnesses, as outbreaks of vaccine-preventable diseases are more common in urban slums. Though the immunization coverage has been steadily increasing, the average level remains far less, which is 62% (NFHS4) than the desired coverage (90%). Objectives: 1) To estimate Immunization coverage in children aged between 12-23 months living in Urban Slum area 2) To study sociodemographic factors influencing immunization coverage & reasons behind m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Similar to a study conducted in urban slums of Western Maharashtra, India, we found that higher education level was found to have a significant relationship with the complete basic provision for children with an OR value of 1.64 [14]. This may be because mothers with higher education have better knowledge, awareness, health-seeking behavior, and decisionmaking capacity than mothers with lower education.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to a study conducted in urban slums of Western Maharashtra, India, we found that higher education level was found to have a significant relationship with the complete basic provision for children with an OR value of 1.64 [14]. This may be because mothers with higher education have better knowledge, awareness, health-seeking behavior, and decisionmaking capacity than mothers with lower education.…”
Section: Discussionsupporting
confidence: 83%